Optimalisasi Kesehatan Maternal dan Bayi: Pengabdian Masyarakat untuk Peningkatan Keselamatan Kehamilan, Persalinan, Nifas dan Bayi Baru Lahir Serta Pencegahan Stunting (Inovasi Sosial : Jurnal Pengabdian Masyarakat, 2026)
Data from the 2020 LFSP (Long Form Population Census) recorded a maternal mortality ratio of 189 per 100,000 live births, while the infant mortality rate was recorded at 16.85 per 1,000 live births. The causes of maternal mortality were hemorrhage, preeclampsia/eclampsia, infection, prolonged labor, and miscarriage. Meanwhile, the majority of infant deaths were due to low birth weight, asphyxia, and infection at birth. Stunting remains a particular concern in Tegal City. Various measures have been taken, and the stunting rate has decreased to around 13.8% according to data from early 2025. This PKM is expected to increase public knowledge on caring for pregnant women, women in labor, postpartum women, and newborns, as well as preventing stunting in children, thereby reducing maternal and infant mortality rates. The methods used in this activity include health education and outreach with a promotive and preventive approach, targeting pregnant women and mothers with infants and toddlers. Community service was held on Wednesday, December 17, 2025, from 8:30 a.m. to 12:00 p.m. at the Boegenvil Health Center in Cabawan Village, Tegal City, with 53 participants. The results of this activity showed an increase in the level of knowledge of the participants, from 11 people with a good level of knowledge to 41 people after receiving counseling, with 3 participants still having a low level of knowledge.